A Cross-Sectional Study of First Hundred Cases of Rhino-Orbital-Cerebral Mucormycosis Admitted at a Tertiary Care Hospital - Lakhan Poswal; G L Bunkar; Rupa Sharma; Ashish Jain; Neera Samar; Navneet Mathur; Maninder Singh; Pratap Bhan Kaushik (Wolters Kluwer Medknow Publications, 2022)
Background: With the second wave of coronavirus disease (COVID-19) Rhino Orbito Cerebral Mucormycosis (ROCM) has emerged as an epidemic in India. Early suspicion and management can reduce disfigurement and mortality. Objectives: To identify the demographic and clinical profile of ROCM, its association with COVID-19 and other predisposing factors. Methods: Hospital Based Cross Sectional Observational study on first hundred consecutive patients with signs and symptoms and radiological findings suggestive of ROCM. Data collected from patient records and analyzed. Results: Out of hundred, 72 patients were Males, 74 from rural areas, all were above eighteen years age, 35 presented with orbital and 27 with facial manifestations of ROCM. Main predisposing factors were history of COVID-19 (71%), previous hospitalization (48%), in Intensive Care Unit (5%) systemic corticosteroid therapy (48%), Diabetes, uncontrolled (45%) and new (21%). Conclusions: ROCM presented with orbital and facial manifestations. Main predisposing factors were Diabetes, COVID-19 and systemic steroids.